2022
DOI: 10.32861/jbr.81.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Some Medicinal Plants on Common Multidrug-Resistant Bacterial Isolates from Some Patients Attending Federal Medical Center, Birnin Kebbi, Nigeria

Abstract: Bacterial infections are among the major causes of morbidity and mortality worldwide. The development of drug resistance to most antibiotics by bacterial species are pandemic, these necessitate the urgent need to search for new antibacterial drugs from the natural sources. Hence this research was aimed at evaluating the antibacterial activity of some medicinal plants on the most commonly drug resistant bacterial isolates from some patients attending Federal Medical Center (FMC) Birnin Kebbi, Nigeria. An ethno-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…This is because smaller NPs have a greater surface area and a greater potential for cell interaction. Silver nanoparticles may inhibit the formation of listeria biofilm (Sani et al 2022). Similar research demonstrated that Silver and CuO can eradicate L. monocytogenes (Milillo et al 2012).…”
Section: Nanoparticlesmentioning
confidence: 74%
“…This is because smaller NPs have a greater surface area and a greater potential for cell interaction. Silver nanoparticles may inhibit the formation of listeria biofilm (Sani et al 2022). Similar research demonstrated that Silver and CuO can eradicate L. monocytogenes (Milillo et al 2012).…”
Section: Nanoparticlesmentioning
confidence: 74%
“…An in vitro study on the methanolic extract from the root of L. laxiflorus showed the antibacterial activity against Staphylococcus aureus, Pseudomonas aeruginosa , and Escherichia coli. A qualitative phytochemical screening test on the methanolic extract from the root of L. laxiflorus revealed the presence of flavonoids, alkaloids, saponins, tannins, phenols, and steroids [ 15 ].…”
Section: Introductionmentioning
confidence: 99%